'[T]o hook my rambling verse on': Byron's Rhyme, Improvisation, and Motivation. Issue 2 (December 2019) - Jones, Christine Kenyon
Abstract : The focus of this article is Byron's deployment of rhyme as a component of his improvisational and compositional techniques: especially (in the two-hundredth anniversary year of the publication of the first two cantos of Don Juan ) his use of ottava rima . In particular, it addresses his claim—serious or not—to have relied for his rhymes on 'Walker's Lexicon': John Walker's 1775 Dictionary of the English Language, Answering at once the Purposes of Rhyming, Spelling and Pronouncing . Through a close reading of some early drafts of stanzas from Canto I of Don Juan (begun in July 1818 and published with Canto II in July 1819), it attempts to reconstruct some of the thought processes Byron may have pursued in originating, building and shaping his verse through rhyme, even while he was also claiming, creating and maintaining a deliberate stylistic effect of spontaneity and immediacy.